Modeling Longitudinal Dispersion in Variable Porosity Porous Media: Control of Velocity Distribution and Microstructures - Gouze, Philippe; Puyguiraud, Alexandre; Porcher, Thierry; Dentz, Marco (Frontiers in Water, 2021)
Hydrodynamic dispersion process in relation with the geometrical properties of the porous media are studied in two sets of 6 porous media samples of porosity $θ$ ranging from 0.1 to 0.25. These two sets of samples display distinctly different evolutions of the microstrutures with porosity but share the same permeability trend with porosity. The methodology combines three approaches. First, numerical experiments are performed to measure pre-asymptotic to asymptotic dispersion from diffusion-controlled to advection-controlled regime using Time-Domain Random Walk solute transport simulations. Second, a porosity-equivalent network of bonds is extracted in order to measure the geometrical properties of the samples. Third, the results of the direct numerical simulations are interpreted as a Continuous Time Random Walk (CTRW) process controlled by the flow speed distribution and correlation. Theses complementary modelling approaches allows evaluating the relation between the parameters of the conceptual transport process embedded in the CTRW model, the flow field properties and the pore-scale geometrical properties. The results of the direct numerical simulations for all the 12 samples show the same scaling properties of the mean flow distribution, the first passage time distribution and the asymptotic dispersion versus the P\'eclet number than those predicted by the CTRW model proposed by~\citet{Puyguiraud_PRL_2021}. It allows predicting the asymptotic dispersion coefficient $D^*$ from $Pe =1 $ to the largest values of $Pe$ expected for laminar flow in natural environments ($Pe ≈ 4000$). $D^* \propto Pe^{2-α}$ for $Pe \ge Pe^{crit}$, where $α$ can be inferred from the Eulerian flow distribution and $Pe^{crit}$ depends on porosity. The Eulerian flow distribution is controlled by the distribution of fractions of fluid flowing at each of the pore network nodes and thus is determined mainly by the distribution of the throat radius and the coordination number. The later scales with the number of throats per unit volume independently on the porosity. The asymptotic dispersion coefficient $D^*$ decreases when porosity increases for all P\'eclet values larger than 1 due to the increase with porosity of both $α$ and the flow speed decorelation length.